Normal values and reference ranges for left atrial strain by speckle-tracking echocardiography: the Copenhagen City Heart Study. (11th October 2021) - Nielsen, Anne Bjerg; Skaarup, Kristoffer Grundtvig; Hauser, Raphael; Johansen, Niklas Dyrby; Lassen, Mats Christian Højbjerg; Jensen, Gorm Boje; Schnohr, Peter; Møgelvang, Rasmus; Biering-Sørensen, Tor
Abstract: Aims : Left atrial (LA) function assessed by two-dimensional speckle-tracking echocardiography has shown increasing clinical and prognostic significance. We sought to establish age- and sex-based normative values of LA strain in the general population and to assess the prognostic yield of lower limits of normality of LA strain in relation to future atrial fibrillation (AF). Methods and results : We determined normative values of peak atrial longitudinal strain (PALS), peak atrial contraction strain (PACS), and LA strain during the conduit phase (LACS) in 1641 healthy participants included in the fifth Copenhagen City Heart Study. In a secondary analysis, a validation cohort of 2016 participants, regardless of health status, were included to assess the prognostic value of the established reference values. In the healthy cohort, median age was 46 years (interquartile range 32–57), 62% were female. Median PALS, PACS, and LACS and corresponding limits of normality in the healthy participants were 39.4% (23.0–67.6%), 15.5% (6.4–28.0%), and 23.7% (8.8–44.8%), respectively. There was a tendency of lower values of PALS and LACS in males and older participants, while PACS tended to increase with advancing age. The established lower limits of normality showed high specificity (range 93–94%) regarding future AF, implying a low risk of developing AF in participants with LA strain above the lower limits of normality in their respective sex and age group. Conclusion : We report normal values for LA strain stratified by sex and age. The lower limits of normality showed high specificity regarding future AF. Graphical Abstract: